2005
DOI: 10.1534/genetics.104.034983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Leucine Uptake by tor1+ in Schizosaccharomyces pombe Is Sensitive to Rapamycin

Abstract: TOR protein kinases are key regulators of cell growth in eukaryotes. TOR is also known as the target protein for the immunosuppressive and potentially anticancer drug rapamycin. The fission yeast Schizosaccharomyces pombe has two TOR homologs. tor1 ϩ is required under starvation and a variety of stresses, while tor2 ϩ is an essential gene. Surprisingly, to date no rapamycin-sensitive TOR-dependent function has been identified in S. pombe. Herein, we show that S. pombe auxotrophs, in particular leucine auxotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 53 publications
7
110
2
2
Order By: Relevance
“…To determine whether the previously demonstrated rapamycin inhibition of permease expression is Bhd dependent, we treated wild-type and ⌬bhd S. pombe with the same dose of rapamycin used by Weisman et al (100 ng/ml), and measured the expression of the four permeases (869.10 ϩ , 7G5.06 ϩ , isp4 ϩ , and isp5 ϩ ) using real-time RT-PCR. In contrast to the work of Weisman et al (25), we found that in wild-type cells, rapamycin increased the expression of the permeases. These rapamycin-induced increases were confirmed by Northern blot for 7G5.06 ϩ and isp5 ϩ (Fig.…”
Section: Permease Expression In Bhd Mutants Is Increased By Expressiocontrasting
confidence: 99%
See 2 more Smart Citations
“…To determine whether the previously demonstrated rapamycin inhibition of permease expression is Bhd dependent, we treated wild-type and ⌬bhd S. pombe with the same dose of rapamycin used by Weisman et al (100 ng/ml), and measured the expression of the four permeases (869.10 ϩ , 7G5.06 ϩ , isp4 ϩ , and isp5 ϩ ) using real-time RT-PCR. In contrast to the work of Weisman et al (25), we found that in wild-type cells, rapamycin increased the expression of the permeases. These rapamycin-induced increases were confirmed by Northern blot for 7G5.06 ϩ and isp5 ϩ (Fig.…”
Section: Permease Expression In Bhd Mutants Is Increased By Expressiocontrasting
confidence: 99%
“…In S. pombe, the effects of rapamycin are not well understood, but it is believed to inhibit both Tor1-and Tor2-related functions and to inhibit the expression of isp5 ϩ , 7G5.06 ϩ , and 869.10 ϩ permeases (25,29). To determine whether the previously demonstrated rapamycin inhibition of permease expression is Bhd dependent, we treated wild-type and ⌬bhd S. pombe with the same dose of rapamycin used by Weisman et al (100 ng/ml), and measured the expression of the four permeases (869.10 ϩ , 7G5.06 ϩ , isp4 ϩ , and isp5 ϩ ) using real-time RT-PCR.…”
Section: Permease Expression In Bhd Mutants Is Increased By Expressiomentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Involvement of the Tor1 complex in stress response, mating and leucine uptake has been reported. 22,25,30 In contrast to fission yeast, budding yeast (S. cerevisiae) appears to differ with the mammalian system in some key aspects (Fig. 1).…”
Section: Fission Yeast Is a Model System For The Analysis Of The Tor mentioning
confidence: 99%
“…Although Tor2p, like Rhb1p, is essential for growth, tor1⌬ cells are sterile and unable to arrest in G 1 in response to nitrogen starvation (26,27). Tor1p also is implicated in the regulation of stress response and uptake of some amino acids (26)(27)(28). We recently have reported that fission yeast Rhb1p associates with Tor2p (25).…”
mentioning
confidence: 99%